Strategic financial management: Lessons from seasoned equity offerings - FU, Fangjian (Institutional Knowledge at Singapore Management University, 2021)
Each of today's three dominant academic theories of capital structure has trouble explaining the financing behavior of companies that have seasoned equity offerings (SEOs). In conflict with the tradeoff theory, the authors’ recent studies of some 7,000 SEOs by U.S. industrial companies over the period 1970-2017 notes that the vast majority of them—on the order of 80%—had the effect of moving the companies away from, rather than toward, their target leverage ratios. Inconsistent with the pecking-order theory, SEO issuers have tended to be financially healthy companies with low leverage and considerable unused debt capacity. And at odds with the market-timing theory, SEOs appear to be driven more by the capital requirements associated with large investment projects than by favorable market conditions. The authors’ findings also show that, in the years following their stock offerings, the SEO companies tend to issue one or more debt offerings, which have the effect of raising their leverage back toward their targets.Whereas each of the three theories assumes some degree of shortsightedness among financial managers, the authors’ findings suggest that long-run-value-maximizing CFOs manage their capital structures strategically as opposed to opportunistically. They consider the company's current leverage in relation to its longer-run target, its investment opportunities and long-term capital requirements, and the costs and benefits of alternative sequences of financing transactions. This framework, which the authors call strategic financial management, aims to provide if not a unifying, then a more integrated, explanation—one that draws on each of the three main theories to provide a more convincing account of the financing and leverage decisions of SEO issuers.